Formulasi sediaan body butter ekstrak etanol bunga rosella (Hibiscus sabdariffa L.) sebagai pelembab kulit - Diana, Vivi Eulis; Abadi, Hafizhatul; Andry, Muhammad (Journal of Pharmaceutical and Sciences, 2023)
Background: Body butter is a semi-solid preparation with the highest fat content, so it is very thick and has a consistency very similar to butter, and has a better ability to nourish the skin than body lotion. In addition, body butter itself is perfect for eliminating reddish lines that usually appear on the skin or commonly called strechmarks. Objective: To test the physical quality stability of the concentration of rosella flower ethanol extract formula (Hibiscus sabdariffa L.) in body butter preparations that have been made. Method: The method used is laboratory experimental. Research includes plant extraction, plant identification, making simplisia, phytochemical screening, making ethanol extract, body butter preparation formulation, and quality stability testing of preparations. The sample used in this study was Rosella Flower (Hibiscus sabdariffa L). The research data was analyzed using the SPSS program, namely the Anova test. Result: Rosella flower ethanol extract (Hibiscus sabdariffa L.) has a semisolid form, homogeneous no coarse particles, with a pH value of the preparation ranging from 6.3-6.4, non-irritating, and can moisturize the skin. But it is not stable with cycling test method storage and stable at room temperature for 4 weeks. The best formula of body butter preparation from ethanol extract of rosella flower (Hibiscus sabdariffa L.) to moisturize the skin is a concentration of 3%. Conclusion: Rosella flower ethanol extract (Hibiscus sabdariffa L.) can be formulated in body butter preparations. It is recommended that future researchers formulate it into other preparations in the same concentration using the same plant from rosella flowers (Hibiscus sabdariffa L.).